Strategi Budaya Organisasi Bawaslu Kabupaten Bekasi Dalam Merespon Indeks Kerawanan Pemilu 2024 - Anwar, Fadilla; Fahmi, Abdi Zul; Andriyansyah, Riki; Ardiansyah, Reksa; Ruhana, Faria (Bahasa Indonesia, 2024)
The 2024 general election in Indonesia has become a global concern due to the potential vulnerabilities that could occur. Bawaslu Bekasi Regency as an organization that plays an important role in the election process, must have an effective strategy and culture in dealing with this vulnerability index. This study aims to determine the strategy and organizational culture of the Bekasi Regency Bawaslu in responding to the 2024 election vulnerability index. The results showed that Bawaslu Bekasi Regency has developed a solid strategy and culture in dealing with the vulnerability index, including improving the quality of human resources, improving communication with the community, and improving security and order. These results show that the Bekasi Regency Bawaslu is ready to face the 2024 election vulnerability index with an effective strategy and culture.